Developing dementia health promotion materials for Indigenous people in an urban Northern Ontario community - Webkamigad, Sharlene (Laurentian University of Sudbury, 2017)
This thesis considers health promotion materials on dementia for Indigenous people using health literacy and cultural safety as guiding frameworks. The author examined the question “How can we develop health promotion materials about dementia to meet the needs of Indigenous peoples living in urban Northern Ontario?” using two decolonized approaches to community-based participatory action research. Two-eyed seeing combines biomedical information with Indigenous knowledge to develop fact sheets. An understanding of local tribal teachings guided the research locally. Methods involved qualitative data analysis of two focus groups and five one-on-one interviews exploring the fact sheets’ appropriateness. Results suggest the need for a shared understanding of Indigenous and Western cultures; improved cross-cultural communication; the importance of grounding health promotion materials in culture; and, strategies for dementia awareness in Indigenous health literacy. These research findings can be translated to inform policy and practice through key recommendations regarding the development of health promotional materials. Master of Arts (MA) in Interdisciplinary Health